Electromagnetic shielding effectiveness of three-dimensional multilayered interlaced woven fabrics using stainless steel fibers - Brigita Kolcavová Sirková; Veronika Tunáková; Maros Tunák; Karol Jezik (Heliyon)
This study explores and discusses the design, the manufacturing and the morphology of three-dimensional (3D) multilayered weft interlaced woven fabrics using stainless steel fibers on the electromagnetic shielding efficiency (SE). Design solutions of 3D multilayered interlaced fabrics in relation to electromagnetic shielding efficiency are still not sufficiently investigated. Moreover, this study aims to analyze the differences in the internal geometry of 3D multilayered weft interlaced fabrics with different number of layers and frequency of connecting points in multilayered woven fabrics on electromagnetic SE. For this study, the input staple yarn 2 × 20 tex (mixed 80 % polyester/20 % stainless steel fibers) is used for production of approximately 28 types of different 3D multilayer weft interlaced woven fabrics (two and three-layer), with connecting points ranging from 0.5 cm × 0.5 cm–5 cm × 5 cm. The comparison of internal fabric microstructures indicates statistically significant differences in relation to SE, and this contribution extends the theoretical guidance of woven fabric construction with the design and production of special 3D multilayered interlaced fabrics with controlled SE.